2014
DOI: 10.1371/journal.pone.0111707
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping and QTL Analysis of Growth-Related Traits in Pinctada fucata Using Restriction-Site Associated DNA Sequencing

Abstract: The pearl oyster, Pinctada fucata (P. fucata), is one of the marine bivalves that is predominantly cultured for pearl production. To obtain more genetic information for breeding purposes, we constructed a high-density linkage map of P. fucata and identified quantitative trait loci (QTL) for growth-related traits. One F1 family, which included the two parents, 48 largest progeny and 50 smallest progeny, was sampled to construct a linkage map using restriction site-associated DNA sequencing (RAD-Seq). With low c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 65 publications
3
27
0
1
Order By: Relevance
“…Other studies have reported heritability estimates for weight ranging from 0.1 to 0.5 in C. gigas ( Hedgecock et al, 1991 ; Sheridan, 1997 ; Langdon et al, 2003 ; Evans and Langdon, 2006 ). Our results are consistent with heritability estimates described for shell measurements, e.g., Li et al (2011) reported values of 0.149–0.402 for SH in C. gigas at 12 months of age, while Kong et al (2015) described estimates of 0.49 for SH and 0.36 for SL, and Xu et al (2017) reported heritability values of 0.18 for SH and 0.25 for SL. These results imply that growth can potentially be improved by selective breeding.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies have reported heritability estimates for weight ranging from 0.1 to 0.5 in C. gigas ( Hedgecock et al, 1991 ; Sheridan, 1997 ; Langdon et al, 2003 ; Evans and Langdon, 2006 ). Our results are consistent with heritability estimates described for shell measurements, e.g., Li et al (2011) reported values of 0.149–0.402 for SH in C. gigas at 12 months of age, while Kong et al (2015) described estimates of 0.49 for SH and 0.36 for SL, and Xu et al (2017) reported heritability values of 0.18 for SH and 0.25 for SL. These results imply that growth can potentially be improved by selective breeding.…”
Section: Resultssupporting
confidence: 91%
“…Global production of this species reached ∼0.6 M tones in 2016 ( FAO, 2018 ). Given its importance, several selective breeding programs based on family and mass selection have been conducted for the improvement of economically important traits such as body weight, growth rate, survival and yield ( Langdon et al, 2003 ; Evans and Langdon, 2006 ; Li et al, 2011 ; de Melo et al, 2016 ), showing an improvement of the target traits after 1–5 generations. As with other aquaculture species, the recent development of genomic tools opens up the possibility for incorporating genetic markers into breeding programs via genomic selection, resulting in improved selection accuracy and genetic gain ( Goddard and Hayes, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…This present genetic map also significantly improved our previous linkage map (Zhu et al, 2014) by both resolution and accuracy, which would be useful for QTL mapping and identification of potential genes for growth in bighead carp. Genetic linkage maps with more markers may have a larger map size, but other factors such as chromosome interferences may also affect the size of a genetic linkage map (Li and He, 2014;Sun and Liang, 2004). The total length of this new linkage map shorter than the previous map may be because different chromosome interferences derived from interspecific hybridization (Zhu et al, 2014) and intraspecific cross (this study).…”
Section: Genetic Linkage Mapmentioning
confidence: 81%
“…In addition, RAD‐like techniques have been very popular for marker discovery and QTL mapping in bivalve shellfish including Chinese scallop ( Argopecten irradians ; Jiao et al . ), Akoya pearl oyster ( Pinctata fucata ; Li & He ; Shi et al . ), variously coloured abalone ( Haliotis diversicolor ; Ren et al .…”
Section: Applications Of Rad Sequencing In Aquaculturementioning
confidence: 99%